The Vestibular Column in the Mouse: A Rhombomeric Perspective - Diaz, Carmen; Glover, Joel C. (Frontiers in Neuroanatomy, 2022)
The vestibular column is located in the hindbrain between the sensory auditory (dorsal) and trigeminal (ventral) columns, spanning rhombomeres r1 (or r2) to r9. It contains the vestibular nuclear complex that receives sensory innervation from the labyrinthine end organs in the inner ear. Gene expression studies and experimental manipulations of developmental genes, particularly Hox genes and other developmental patterning genes, are providing insight into the morphological and functional organization of the vestibular nuclear complex, particularly from a segmental standpoint. Here, we will review studies of the classical vestibular nuclei and of vestibular projection neurons that innervate distinct targets in relation to individual rhombomeres and the expression of specific genes. Studies in different species have demonstrated that the vestibular complex is organized into a hodological mosaic that relates axon trajectory and target to specific hindbrain rhombomeres and intrarhombomeric domains, with a molecular underpinning in the form of transcription factor signatures, which has been highly conserved during the evolution of the vertebrate lineage.